2003
DOI: 10.1038/sj.mp.4001205
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia, neurodevelopment and corpus callosum

Abstract: The Zeitgeist favors an interpretation of schizophrenia as a condition of abnormal connectivity of cortical neurons, particularly in the prefrontal and temporal cortex. The available evidence points to reduced connectivity, a possible consequence of excessive synaptic pruning in development. A decreased thalamic input to the cerebral cortex appears likely, and developmental studies predict that this decrease should entail a secondary loss of both longand short-range cortico-cortical connections, including conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
103
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(118 citation statements)
references
References 148 publications
8
103
1
Order By: Relevance
“…Deficits may only emerge when information of one hemisphere is not sufficient to solve a cognitive problem. These results suggest that cognitive impairments as observed in developmental or psychiatric disorders might also be only fully comprehensible by an understanding of abnormal interhemispheric communication systems, although genetic and/or environmental factors may primarily cause aberrations of intrahemispheric circuits 6,7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deficits may only emerge when information of one hemisphere is not sufficient to solve a cognitive problem. These results suggest that cognitive impairments as observed in developmental or psychiatric disorders might also be only fully comprehensible by an understanding of abnormal interhemispheric communication systems, although genetic and/or environmental factors may primarily cause aberrations of intrahemispheric circuits 6,7 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, even profoundly lateralized cognitive functions, such as speech processing, benefit from efficient interhemispheric communication 2 . On the other hand, developmental disorders like autism 3 , dyslexia 4 or schizophrenia 5 are characterized by untypical cerebral lateralization patterns as well as structural peculiarities of the corpus callosum that are related to cognitive impairments [6][7][8][9][10] . Although several studies suggest a relationship between functional lateralization and structural organization of commissural systems, for example 11,12 , the functional and developmental relationships remain controversial 13 .…”
mentioning
confidence: 99%
“…42 The pathophysiological symptoms of schizophrenia suggest a potential dysfunction in several brain regions that may also include neuronal and synaptic connections to temporal and frontal cortical regions, which are involved in higher cognitive functions, such as language and working memory. 43,44 In addition, MRI and post-mortem histopathological studies have revealed structural abnormalities in these cortical regions. 45,46 Interestingly, expression studies in mice showed a markedly reduced expression of PLXNA2 in the neocortex after birth, suggesting an important role in the development of neuronal connection patterns, especially in regions of the cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cortex and hippocampus are regions strongly implicated in the pathophysiology of schizophrenia. [35][36][37][38] It was previously reported that density of neurons can be significantly reduced in certain layers of the cortex of schizophrenics. For example, schizophrenic subjects showed a significant decrease in density of nonpyramidal neurons in layer II and pyramidal neurons in layer IV of the anterior cingulated cortex.…”
Section: Discussionmentioning
confidence: 99%